Chloride Penetration into Concrete under the Coupling Effects of Internal and External Relative Humidity - Fangzhi Zhu; Zhiming Ma; Mingmin Zhang (Advances in Civil Engineering)
Chloride penetration frequently happens in an unsaturated concrete; in this case, the chloride migration is under the coupling effects of internal moisture and external relative humidity (RH). Various chloride attack tests were designed in this paper to investigate the effects of internal moisture and external RH (50–100%) on the chloride penetration into an unsaturated concrete, and the chloride content was determined to quantify the chloride migration in concrete. The results highlighted that there was a good correlation between the chloride penetration into concrete and its internal RH. The chloride ion was difficult to penetrate into concrete when its internal RH was below 50%; however, the chloride penetration rate increased when the internal RH of concrete was above 75%, and the chloride migration increased with increasing RH and exposure duration. Water evaporation in concrete increased with decreasing external RH, and an obvious increase in the surface chloride content may be observed when external RH was 50%; however, when external RH was above 75%, the inner chloride content increased and surface chloride content decreased with increasing exposure duration. Simulating the chloride penetration under wet-dry cycling, the water migration resulted in an increase in the surface chloride content and a decrease in the inner chloride content, and the chloride crystal precipitated on the surface of concrete with a high w/c ratio.